Utilization of Plants at FMIPA UNM as a Learning Resource for Plant Taxonomy Subjects - Muliana GH (EduLine: Journal of Education and Learning Innovation, 2023)
This research aims to determine the types of plant species found in the FMIPA UNM environment which can be used as learning resources in higher plant botany courses. This research was carried out in the FMIPA UNM environment from August to October 2023. Exploration and documentation of plants was carried out from September to October 2023. The target of this research was higher plant species including angiosperms and gymnosperms found in the FMIPA UNM environment. This research uses descriptive analytical methods. The data collection technique was carried out exploratively. The results of the research show that there are more than ninety-seven plant species found in the FMIPA UNM environment originating from fifty-five families originating from the plant groups angiosperms (closed seed plants) and gymnosperms (open seed plants), where these plants can used as a learning resource in higher plant botany courses. Keywords: Plants, Learning Resources, Botany of Higher Plants